Factors affecting cryptocurrency adoption: Extending the UTAUT2 model with financial literacy and trust - Salim, Hans Christian; Angriawan, Ricky; Widuri, Rindang (Edelweiss Applied Science and Technology, 2025)
The adoption of cryptocurrency has accelerated due to technological advancements and growing public interest in digital assets. Cryptocurrencies like Bitcoin and Ethereum use blockchain technology to enable decentralized and transparent transactions. While often viewed as investment tools, this study focuses on users’ intentions to adopt cryptocurrency for peer-to-peer transactions, decentralized applications, and digital financial services. The research extends the Unified Theory of Acceptance and Use of Technology 2 (UTAUT2) by incorporating trust and financial literacy. Key constructs include performance expectancy, effort expectancy, social influence, facilitating conditions, trust, price value, and financial literacy. Using a quantitative approach, survey data from Indonesia were analyzed with Structural Equation Modeling–Partial Least Squares (SEM-PLS). Results show that the extended UTAUT2 model explains 63.5% of the variance in behavioral intention. Performance expectancy, trust, and price value significantly influence adoption, with trust being the strongest predictor. Financial literacy was not significant, suggesting that awareness of risks may lead to non-adoption. Regulators should establish transparent policies to foster trust, while developers should emphasize usability and clear benefits. For users, the findings support that not adopting cryptocurrency despite being financially literate can be a rational and informed decision.